Recent Advances in Drugs and Vaccines for COVID-19 - Tang, Meiqin; Yao , Xinhuang; Tian , Faqing; Jiang , Man; Yang , Jianshe (Diagnostic and Treatment Advances in COVID-19 and SARS-CoV-2, 2023)
Several potential COVID-19 therapeutic approaches and SARS-CoV-2 vaccines have been investigated, and final clinical reports are gradually becoming available. In this mini-review, we discussed the history of selected potential therapeutic drugs and newly designed vaccines, as well as other approaches for the COVID-19 treatment, and made a primary evaluation of their clinical effects. Finally, according to the nature of coronavirus we posed a promising design to against the SARS-CoV-2 by the chemi-physical methods through carbon nano-materials modification.